Deregulasi Qanun dan Kebijakan Penanaman Modal di Aceh - Said Syahrul Rahmad (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2017)
With the establishment of the Regulation No. 11 on 2006 about Aceh Government it continues to make efforts to improve the economy in Aceh. The Government has prepared a set of regulations that Qanun No. 4 on 2013 about the Amendment of Qanun No. 5 of 2009 on Investment. In addition, the Aceh government has also made policies to promote human resources and natural resources of international and regional level to bring investors invest in Aceh. In conducting strategies and efforts to attract investors to Aceh it remain guided by the standard procedure of good governance as stated in The Regulation No. 11 on 2006 about the Government of Aceh, Article 165 point (2) said that the Aceh Government and district / city governments in accordance with authority may attract foreign tourists and provide licenses related to investment in domestic investment, foreign investment, exports and imports with regard norms, standards, and procedures that apply nationally. Through the Investment and Promotion department of Aceh has made various efforts to bring investors to Aceh. Investment and Promotion department of Aceh has been targeted by the end of 2017 that it would become one of the Aceh province of Indonesia investment destination through the motto